Organizational culture and organizational learning: Role of environmental culture and business strategy in SMEs - Ntoto, Flavien Mpasi Ya; Cavusoglu, Behiye; Ismael, Goran Yousif (Asian Development Policy Review, 2024)
The study aims to empirically examine the effect of organizational culture and organizational learning on the organizational performance of small and medium-sized enterprises (SMEs) operating in the various sectors of the Democratic Republic of Congo (DRC). The study also examines the moderating role of environmental culture and mediating role of business strategy on organizational performance. Using partial least squares structural equation modelling (PLS-SEM) and bootstrapping procedures, data from 131 SME owners and managers was analysed. Performance indices, including sales, pre-tax profits, and workforce size from 2008 to 2013, were utilized. Regression and analysis of variance (ANOVA) were conducted to examine the relationship between strategy and organizational performance. Findings suggest a positive and significant direct effect of organizational culture and learning on SME performance, with an indirect effect mediated by business strategy. Additionally, business strategy was found to have a significant impact on organizational performance. It was found that business strategy had a statistically significant impact on the organization. As a practical implication, the study recommends that SMEs adopt a sufficient strategy and leverage cost leadership to improve growth and induce better organizational performance.